Flora and phytogeography of the Czech Republic - Kaplan, Zdeněk
A review of the flora and phytogeography of the Czech Republic is given. The diversity of plants in this country reflects its geographic position in the centre of Europe, local natural conditions and the effect of intense human activity on the landscape. The Czech flora includes 148 families, 916 genera, 3557 species (plus 194 additional subspecies) and 609 hybrid vascular plants. Families richest in species are Asteraceae (662 species), Rosaceae (316), Poaceae (275), Fabaceae (170), Brassicaceae (148), Cyperaceae (127), Lamiaceae (112), Caryophyllaceae (108) and Apiaceae (100). Most of these species are native and 36.0% are alien. The spectrum of life-forms is dominated by hemicryptophytes (45.7%), followed by therophytes (22.3%), phanerophytes (14.4%), geophytes (9.3%), chamaephytes (5.1%) and hydrophytes (3.2%), while the percentage of epiphytes is negligible (only two species). Several species that occur in the Czech Republic are relicts from glacial and early postglacial periods. Examples of arctic, boreal, alpine, steppe and other sorts of relicts are listed. Because of the relatively small size of this country and the considerable climatic and vegetational changes caused by glaciations, which repeatedly eliminated the local flora, endemism is relatively low in the Czech Republic. All endemics are of Quaternary age (neoendemics). A revised list of endemic species and subspecies includes 74 taxa endemic to the Czech Republic and adjacent border regions, which is 2% of the total vascular plant diversity. Of these, 48 taxa are strictly Czech endemics (defined by the borders of the country), the distributions of the other 26 taxa extend slightly beyond the borders of this country (mostly by less than 1 km) in the summit areas of the Krkonoše/Karkonosze Mts and/or in the Králický Sněžník/Śnieżnik Kłódzki Mts. Hieracium and Sorbus are the genera with the greatest number of endemics (25 and 11 species and subspecies, respectively). Patterns in the distribution and occurrence of endemics in different types of ...